Strategi Manajemen Komunikasi Ormas Hindu dalam Membangun Representasi Keagamaan di Instagram - Suardana, I Ketut Putu; Wastawa, I Wayan; Dasih, I Gusti Ayu Ratna Pramesti (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This study examines the digital communication strategies of Hindu mass organizations (ormas) in Lombok in building religious representation through the Instagram platform. Social media has become a new potential space to convey Hindu religious teachings more widely and interactively. This study analyzes the content of the official accounts of four Hindu mass organizations, namely PHDI, KMHDI, Prajaniti, and Peradah, with a focus on the types of messages, visual forms, and communication patterns used. The results of the study show that Prajaniti Lombok is the most active and strategic mass organization in building religious representation digitally. Through educational reel content and attractive visuals, Prajaniti is able to raise narratives of Hindu teachings in a contextual and relevant manner to young audiences. Meanwhile, PHDI and KMHDI are still dominant in the use of informative and ceremonial content, while Peradah tends to be limited to formal speech. This study suggests the importance of strengthening the digital capacity of Hindu mass organizations in Lombok through training in managing social media based on religious narratives, as well as collaboration in producing creative and contextual content. An effective digital communication strategy will strengthen the role of Hindu mass organizations in maintaining the existence of dharma teachings amidst the dynamics of today's digital space.